Continuous venovenous renal replacement therapy in critically ill patients: A work load analysis. (October 2016) - Houllé-Veyssière, Marjorie; Courtin, Audrey; Zeroual, Norddine; Gaudard, Philippe; Colson, Pascal H.
Summary: Objectives: To evaluate the nursing workload related to two techniques of continuous renal replacement therapy. Research methodology: We analysed retrospectively the nursing work load caused directly by continuous renal replacement therapy in a cohort of patients admitted consecutively over 10 months. Two types of continuous renal replacement therapy have been compared: dialysis with regional citrate anticoagulation and haemodiafiltration with systemic heparin coagulation. Setting: Academic Hospital Intensive Care Unit. Main outcome measures: The nursing workload was defined by the time spent in the management of continuous renal replacement therapy, including preparation of the circuit and related biological controls. Results: 60 patients underwent a total of 202 sessions of continuous renal replacement therapy. The nursing workload as expressed as % time of nursing care was similar (12.3 [9.4–18.8] vs 13.4 [11.7–17.0] %, for haemodiafiltration and dialysis respectively, P  = 0.06). However, the distribution of the nursing workload is different: the bigger proportion of care is circuit preparation in haemodiafiltration and biology control in dialysis. Conclusions: Nursing time dedicated to continuous renal replacement therapy is similar whatever the renal replacement therapy technique. However, a longer duration of the filter and a better circuit predictability with dialysis and citrate anticoagulation are potential benefits for nursing workload.